ETHICAL LEADERSHIP AND THE SINICIZATION OF CHINESE BUDDHISM: RE-READING THE CHANLIN BAOXUN AS A MODEL OF MONASTIC GOVERNANCE TODAY - Guangxi ZUO; Chompoo Gotiram (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study reinterprets  Chanlin Baoxun (禪林寶訓) as a foundational text that shapes ethical leadership and institutional governance in Chinese Buddhism from the Song dynasty to the present. Combining philological analysis of classical sources with comparative case studies of Nanputuo and Baoguang Monasteries, it argues that the Baoxun established an enduring paradigm of virtue-based governance that integrates Buddhist self-cultivation with Confucian moral rationality. The research identifies three interrelated principles—self-discipline (de 德), administrative competence (neng能), and social responsibility (gong 公)—that constitute the moral architecture of legitimate monastic authority. The text's internalization of Confucian ethics, particularly li (ritual propriety) and zhong-xiao (loyalty and filiality), illustrates how Sinicization functioned historically as an ethical translation rather than ideological assimilation. Contemporary monasteries continue to embody this legacy through distinct modalities: Nanputuo emphasizes compassion-driven civic engagement, while Baoguang institutionalizes virtue through transparent moral bureaucracy. The findings challenge reductionist readings of Sinicization as state compliance, demonstrating instead a long-standing process of moral localization through which Buddhist institutions negotiate cultural legitimacy and ethical autonomy. The study contributes to broader theories of religious leadership and governance by proposing a "virtue-bureaucracy" model that reconciles charisma, ethics, and institutional order—suggesting that durable authority, whether spiritual or secular, remains a moral achievement grounded in disciplined virtue.